Improving students’reading ability by using question-answer relationship - Rengganis Siwi Amumpuni (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2017)
QAR (Question- Answer Relationship) strategy is a teaching strategy which asks the students to read narrative text and classify question and answer it into each of QAR categories. The objective of this research is to determine whether or not Question Answer Relationship Strategy can improve reading ability of the second semester students of Universitas PGRI Madiun. This research is classroom action research consisting of two cycles. Each cycle consists of four steps. They are planning, action, observation and reflection. The result of this research shows that the students’ reading ability is increase. It can be proven from the mean score of cycle one is 70.56 and cycle two is 75,83. The researcher also found that QAR helps the students to understand the text. The students are interested in answering the question based on the text, are motivated to read the text, and feel not bored in teaching reading process